Responsibilities and Authorities of External Directors in Family-Owned Companies: A Legal and Islamic Perspective - Ria Rindika Oktaviana; Budi Santoso (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
Family businesses account for 72% of enterprises in Indonesia, many of which operate as Limited Liability Companies (LLCs) to gain legal and financial flexibility. However, a significant governance problem arises when appointing external (non-family) directors; the boundaries of their authority and fiduciary responsibilities are often unclear. This ambiguity leads to legal disputes and diminished strategic roles, especially under the dominance of controlling family members. This study examines the boundaries of external directors' responsibilities in family-owned LLCs through the lens of Islamic law and normative jurisprudence. This qualitative research employs normative legal analysis and Islamic law, using academic literature, legal documents, and classical Islamic texts to explore authority within Limited Liability Companies and analyze using a qualitative descriptive approach. The findings indicate that although Law No. 40 of 2007 regulates fiduciary duties and the ultra vires principle, external directors remain vulnerable to the dominance of family owners. From an Islamic perspective, external directors are regarded as trustees who must uphold honesty (ṣidq), trustworthiness (amanah), and justice (‘adl). The study proposes four key solutions: clear articles of association, protective contracts, independent supervisory boards, and Sharia Advisory Boards. These offer a governance model rooted in legal certainty and Islamic ethics, contributing practical insights for regulators, business owners, and directors in Muslim family enterprises.